Additive effect of anemia and renal impairment on long-term outcome after percutaneous coronary intervention. - Thomas Pilgrim; Martina Rothenbühler; Bindu Kalesan; Cédric Pulver; Giulio G Stefanini; Thomas Zanchin; Lorenz Räber; Stefan Stortecky; Simon Jung; Heinrich Mattle; Aris Moschovitis; Peter Wenaweser; et al. (PLoS ONE)
Introduction Anemia and renal impairment are important co-morbidities among patients with coronary artery disease undergoing Percutaneous Coronary Intervention (PCI). Disease progression to eventual death can be understood as the combined effect of baseline characteristics and intermediate outcomes. Methods Using data from a prospective cohort study, we investigated clinical pathways reflecting the transitions from PCI through intermediate ischemic or hemorrhagic events to all-cause mortality in a multi-state analysis as a function of anemia (hemoglobin concentration <120 g/l and <130 g/l, for women and men, respectively) and renal impairment (creatinine clearance <60 ml/min) at baseline. Results Among 6029 patients undergoing PCI, anemia and renal impairment were observed isolated or in combination in 990 (16.4%), 384 (6.4%), and 309 (5.1%) patients, respectively. The most frequent transition was from PCI to death (6.7%, 95% CI 6.1-7.3), followed by ischemic events (4.8%, 95 CI 4.3-5.4) and bleeding (3.4%, 95% CI 3.0-3.9). Among patients with both anemia and renal impairment, the risk of death was increased 4-fold as compared to the reference group (HR 3.9, 95% CI 2.9-5.4) and roughly doubled as compared to patients with either anemia (HR 1.7, 95% CI 1.3-2.2) or renal impairment (HR 2.1, 95% CI 1.5-2.9) alone. Hazard ratios indicated an increased risk of bleeding in all three groups compared to patients with neither anemia nor renal impairment. Conclusions Applying a multi-state model we found evidence for a gradient of risk for the composite of bleeding, ischemic events, or death as a function of hemoglobin value and estimated glomerular filtration rate at baseline.